Damage Simulation of a Random Aggregate Model Induced by Microwave under Different Discontinuous Ratios and Exposure Times. (18th July 2016) - Tang, Yang; Xu, Guobin; Qu, Chunlai; Sun, Liying; Duan, Yu
Abstract : A random aggregate algorithmic method and a numerical model for two-phase materials (composed of quartz and plagioclase) with different discontinuous ratios and irradiation times were studied based on the discrete element method using two-dimensional particle flow code (P F C 2 D ). The results showed that this algorithm can simulate random irregular aggregate shapes. Furthermore, crack initiation and development and the coalescence process of microwave-induced material damage could be predicted using the discrete element method. After analysis of this study, the micro crack originated from the boundary of the high-absorption-phase plagioclase crystal and expanded around the plagioclase, extending into the quartz material. The crack morphology presented a radial network.